Development of snakes and ladders game to increase knowledge of the dangers of smoking among elementary school students: A quasi-experimental study in Malang, Indonesia - Novita Rizky Ramadhani; Windi Chusniah Rachmawati; Moch. Yunus; Nurnaningsih Herya Ulfah (CV Rezki Media, 2025)
Background: The smoking trend has now infected school-age children, with 19.2% of students aged 13-15 years in Indonesia and 2,859 children in Malang City recorded as active smokers, which is influenced by a lack of understanding of the dangers of smoking. Educational interventions such as Snakes and Ladders game-based health promotion media must be developed to build a culture of not smoking from an early age. Objectives: The purpose of the study was to develop educational game media in the form of snakes and ladders as a tool for delivering health information about the dangers of smoking to students of Oro-Oro Dowo Malang State Elementary School. Methods: Research and Development (R&D) type research with a one-group pretest and posttest trial aims to determine the effectiveness of the Snakes and Ladders game as a health promotion media on the dangers of smoking behavior. The subjects needed in this study are media experts, material experts, and students aged 9-13 years as research samples. Results: The average result of increasing knowledge is 0.000 using the Wilcoxon test, so there is a difference in the average value of knowledge in the pretest and posttest data. In the feasibility test results, the assessment results were obtained in the very feasible category. Game media is effective and very feasible to be a health promotion media in efforts to promote the dangers of smoking in children. Conclusions: The Snakes and Ladders game media developed is feasible to be a health promotion media in efforts to promote the dangers of smoking behavior in children. The Snakes and Ladders game media influences increasing students' knowledge of Oro-Oro Dowo Malang State Elementary School about the dangers of smoking. Further research needs to evaluate media's long-term impact and adaptation in various socio-cultural contexts.